1991
DOI: 10.1002/ar.1092300210
|View full text |Cite
|
Sign up to set email alerts
|

Development of esophageal epithelium in the fetal and neonatal mouse

Abstract: Development of the fetal mouse esophageal epithelium was followed using light microscopy, transmission electron microscopy (TEM), scanning electron microscopy (SEM) and radioautography. At 15 days of gestation in the cervical (C), mediastinal (M), and abdominal (A) segments of the esophagus, the epithelium was two or three cells thick, and only cells located in the basal (germinal) layer incorporated tritiated thymidine. Ciliated cells were sparse in all three segments. At 17 days of gestation, longitudinal me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
(48 reference statements)
1
20
0
Order By: Relevance
“…2) (100). In the following days (E13.5-E17.5) the epithelium gradually becomes more layered until there are around four layers of epithelial cells (71,100). During development there is a gradual conversion of a K8-positive cuboidal epithelium to a K14-positive squamous epithelium.…”
Section: Normal Esophageal Morphogenesis and Endodermal Differentiationmentioning
confidence: 99%
“…2) (100). In the following days (E13.5-E17.5) the epithelium gradually becomes more layered until there are around four layers of epithelial cells (71,100). During development there is a gradual conversion of a K8-positive cuboidal epithelium to a K14-positive squamous epithelium.…”
Section: Normal Esophageal Morphogenesis and Endodermal Differentiationmentioning
confidence: 99%
“…Adult mice submitted to a low-calorie diet showed a decrease in the labeling index of the esophageal epithelium (15). Raymond et al (13) observed that the LI of the abdominal (distal) esophageal epithelium of mouse fetuses (18 days of gestation) is 17.9 ± 2. Similar results were obtained in the present study for 14-and 18-day-old fed rats (15.3 ± 3 and 14.0 ± 4.6, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the ultrastructure of the fetal and neonatal esophageal epithelium of the mouse was described in detail but only the proliferative indices of the fetal epithelium were measured (13).…”
Section: Introductionmentioning
confidence: 99%
“…DNA synthesis by cells in different organs has been investigated by many authors using light and electon microscopic autoradiography (Gao et al, 1992;Kong et al, 1992;Raymond et al, 1991;Ma and Nagata, 1990;Nagata and Usuda, 1986;Pelc and Appleton, 1965;Messier and Leblond, 1960;Leblond and Messier, 1958). In spite of the few reports available concerning the DNA synthesis as studied by autoradiography in colon using human (Arsenault and Menard, 1989;Pritchett et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Autoradiographic studies of D N A synthesis demonstrated some evident differences in age-related changes by [ jH]-thymidine incorporation into the different organs and tissues (Duan et al, 1993;Hanai, 1993;Gao et al, 1992;Kong et al, 1992;Olea and Nagata, 1992;Raymond et al, 1991;Arsenault and Menard, 1988;Ma, 1988;Nagata and Usuda, 1986;Leblond and Messier, 1958). Although the studies on D N A synthesis (Morita et al, 1994;Arsenault and Minard, 1989;Buts et al, 1983;Eastwood and Trier, 1974;Chang, 1971;Chang and Lablond, 1971a,b) and cell proliferation (Pritchett et al, 1985;James et al, 1982) of colon epithelium have been carried out, little is known regarding the developmental and age-related changes in colon mucosa.…”
Section: Introductionmentioning
confidence: 99%